An accurate and sensitive Coomassie Brilliant Blue G-250-based assay for protein determination - Grintzalis, Konstantinos; Georgiou, Christos D.; Schneider, Yves-Jacques (Analytical biochemistry, 2015)
In this protocol we present a rapid and sensitive assay for the accurate determination of protein concentration. The assay is a modification of a previous method, and measures minimum 0.2 μg protein.In this protocol we present a rapid and sensitive assay for the accurate determination of protein concentration. The assay is a modification of a previous method, and measures minimum 0.2 μg protein.